2013
DOI: 10.1007/s13760-013-0194-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) in northeast Iran

Abstract: This study aimed to introduce clinical manifestations of patients in northeast Iran with HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) and describe the epidemiological features, as well as risk factors for HTLV-1 infection. This is a cross-sectional study of HTLV-1 infected cases and HAM/TSP patients referred by outpatient neurology clinics as well as Mashhad Blood Transfusion Center from 2005 to 2010. The study comprises 513 cases, including 358 healthy carriers (HCs) and 145 HAM/TSP pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…This increment may be associated with the overtime accumulation of risky sexual exposure or of other transmission risk factors 25 , 26 , 27 . A study showed that among HTLV-I positive blood donor carriers from Iran, males predominated, probably reflecting the lower tradition of female blood donors in this country, whereas among HAM/TSP patients, females predominated 28 . …”
Section: Discussionmentioning
confidence: 99%
“…This increment may be associated with the overtime accumulation of risky sexual exposure or of other transmission risk factors 25 , 26 , 27 . A study showed that among HTLV-I positive blood donor carriers from Iran, males predominated, probably reflecting the lower tradition of female blood donors in this country, whereas among HAM/TSP patients, females predominated 28 . …”
Section: Discussionmentioning
confidence: 99%
“…HTLV-1 infection is endemic in certain parts of the world including southwestern Japan, Central Africa, the Caribbean islands, regions of South America, Australo-Melanesia as well as Khorasan Razavi, a province in northeastern Iran [7]. Based on epidemiological studies, it is estimated that about 2.3-3% of the general population in this province are infected with the HTLV-1 virus [8]. …”
Section: Introductionmentioning
confidence: 99%
“…HTLV-1 is believed to trigger several diseases such as adult T-cell leukemia, HTLV-1-associated myelopathy/tropical spastic paraparesis, sensorimotor polyneuropathy and optic neuritis [8]. There have been a few animal studies regarding HTLV-1 atherogenicity [9].…”
Section: Introductionmentioning
confidence: 99%
“…HTLV‐1 infection may cause diverse neurological presentations such as myelopathy, cerebellar ataxia, dementia, myositis, vertigo, nystagmus, cranial neuropathy, polyneuropathy, optic neuritis, and an amyotrophic lateral sclerosis–like syndrome . Various mechanisms have been proposed regarding the pathogenesis of central nervous system involvement.…”
Section: Introductionmentioning
confidence: 99%
“…1,7 HTLV-1 infection may cause diverse neurological presentations such as myelopathy, cerebellar ataxia, dementia, myositis, vertigo, nystagmus, cranial neuropathy, polyneuropathy, optic neuritis, and an amyotrophic lateral sclerosis-like syndrome. 1,[7][8][9][10] Various mechanisms have been proposed regarding the pathogenesis of central nervous system involvement. Direct attack of the virus to the neurons is not confirmed; however, indirect damage of the nervous system by lymphocytes and autoimmune mechanisms (both humeral and cellular) is a more acceptable hypothesis.…”
Section: Introductionmentioning
confidence: 99%